Peningkatan Kapasitas Anggota Badan Permusyawaratan Desa dalam Teknik Penyusunan Peraturan Desa Pengelolaan Sampah Rumah Tangga - Nasihin, Iing; Nurdin, Nurdin; Yuhandra, Erga; Alpiyah, Lilis Nur; Rachmat, Nurhaliza Ainur (Empowerment, 2023)
The availability of specific laws and regulations, public awareness, and household waste management are factors faced by rural communities in solving household waste problems. BPD is an institution that carries out government functions whose members are representatives of the Village population based on regional representation and are determined democratically. One of the duties and authorities of the BPD is to discuss draft village regulations with the village head. This Community Service aims to provide technical training in drafting village regulations on household waste management to members of the BPD and the Village Government. Community service activities are carried out using 2 (two) approaches, namely Participatory Rural Appraisal (PRA) and Transfer Technology (TT). The scope of the regulation of the Village Regulation includes the duties and authorities of the village government, the formation of a waste bank manager, waste management, supervision and guidance, cooperation and partnership, community participation, financing, incentives, and closing provisions, as well as principles that refer to the principles of responsibility, sustainability, justice, togetherness, participation, and economic value. After the Community service was implemented, the participants showed an increase in their knowledge and capacity in drafting the Village Regulation on household waste management by 42.76%.Ketersedian peraturan perundangan yang spesifik, kesadaran masyarakat, dan tata kelo sampah rumah tangga merupakan faktor-faktor yang dihadapi masyarakat perdesaan dalam menyelesaikan permasalahan sampah rumah tangga. BPD adalah lembaga yang melaksanakan fungsi pemerintahan yang anggotanya merupakan wakil dari penduduk Desa berdasarkan keterwakilan wilayah dan ditetapkan secara demokratis. Salah satu tugas dan wewenang BPD adalah membahas rancangan peraturan desa bersama kepala desa. Tujuan Pengabdian kepada Masyarakat ini adalah untuk memberikan pelatihan teknik penyususan peraturan desa tentang pengelolaan sampah rumah tangga kepada anggota BPD dan Pemerintantahan Desa. Kegiatan pengamdian kepada masyarakat dilakukan dengan 2 (dua) model pendekatan, yaitu Partisipatory Rural Appraisal (PRA) dan Teknologi transfer (TT). Ruang lingkup pengaturan Perdes meliputi tugas dan wewenang pemerintah desa, pembentukan pengelola bank sampah, pengelolaan sampah, pengawasan dan pembinaan, kerjasama dan kemitraan, peran serta masyarakat, pembiayaan, insentif, dan ketentuan penutup. Serta asas-asas yang mengacu pada asas tangung jawab, berkelanjutan, keadilan, kebersamaan, partisipatif, dan nilai ekonomi. Setelah dilaksanakanya PkM peserta menunjukan peningkatan pengetahutan dan kapasitasnya dalam penyususan Perdes pengelolaan sampah rumah tangga sebesar 42,76%.